Linguistic landscape of Balinese society: Birth order and gender distinctions in proper names - Majid Wajdi; I Nyoman Suka Sanjaya; Gusti Ketut Alit Suputra; Ni Nyoman Sarmi; I Ketut Suar Andyana (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
The primary objective of this study is to explore the social and cultural dimensions of Balinese personal names, specifically examining how the order of birth is reflected in the nomenclature. By delving into the historical and cultural context, the study aims to elucidate the societal roles and expectations associated with these names, providing a holistic understanding of their significance within the Balinese community. To achieve a comprehensive analysis, the study employs a combination of document study and the examination of students' attendance lists. Document study involves reviewing historical records, folklore, and other relevant texts to trace the evolution of Balinese naming conventions. Additionally, attending to students' attendance lists offers contemporary insights into the prevalence and adherence to traditional naming practices. The collected data will be subjected to qualitative analysis, utilizing both historical and contemporary perspectives. Thematic analysis will be applied to identify recurring patterns, cultural nuances, and changes over time. Comparative analysis of attendance lists will offer insights into the extent to which traditional naming practices persist in modern Balinese society. By synthesizing the findings from document study and attendance lists, this research aims to provide a nuanced understanding of Balinese naming conventions and their sociolinguistic implications. The study contributes to the preservation of cultural heritage by documenting these unique practices and highlights the importance of recognizing and respecting linguistic diversity in the face of evolving global trends.